The challenges of implementing remote work in the manufacturing industry: The conceptual analysis using SWOT-AHP model - Dean Nelson Mojolou; Faerozh Madli; Ferawati Usman; Nurul Hidayathulzakiyah; Masran Tamin (RSIS International, 2025)
Available online Remote work has revolutionized business operations across industries, yet its implementation in manufacturing presents unique challenges due to the sector's physical and process-driven nature. This research analyzes the conceptual framework for implementing remote work in manufacturing environments, examining challenges and potential solutions. While approximately 65% of manufacturing companies have adopted some remote work, the extent varies significantly based on organizational capabilities and production complexity. The study identifies key challenges, including the physical nature of production processes, technological infrastructure requirements, cybersecurity concerns, communication barriers, and cultural resistance. Critical solutions encompass integrating Industry 4.0 technologies such as the Industrial Internet of Things (IIoT), automation systems, and digital twins, alongside robust cybersecurity measures and comprehensive training programs. The research indicates that successful implementation requires a hybrid operational model where certain functions are performed off-site through digital interfaces while maintaining critical on-site operations. The study will use SWOT-AHP analysis to analyze the key factors in the manufacturing industry. While the transformation presents significant challenges, manufacturers that successfully navigate this transition can achieve enhanced resilience, streamlined operations, and improved access to global talent. The study concludes that effective integration of remote work capabilities will become a crucial competitive advantage in the evolving manufacturing landscape